Climatic tolerances and zoogeography of the late Pleistocene beetle fauna of Beringia - Elias, Scott (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractThe study of fossil beetles has played an important role in the reconstruction of Beringian paleoenvironments. More than 25 fossil localities have yielded Late Pleistocene beetle assemblages, comprising more than 300 species, of which about 147 are predators and scavengers, groups which are suitable for paleoclimatic reconstruction. The author has developed climate envelopes (climatic parameters characterizing the modern localities in which species are found) for these species, in order to perform mutual climatic range pale- otemperature studies. This paper describes the thermal requirements of these beetles, and their zoogeographic history since the interval just prior to the last interglacial period. The fossil assemblages include 14 arctic and alpine species, 66 boreo-arctic species, and 68 boreal and temperate species. The greatest percentage of species with restricted thermal requirements occurs in the arctic and alpine group. The majority of boreo-arctic and boreal and temperate species have very broad thermal requirements. Based on modern distribution and the North American fossil record, it appears that some species resided exclusively in Beringia during the Late Pleistocene. These Beringian species comprise 64 % of the arctic and alpine species found in the fossil assemblages, 34 % of the boreo-arctic species, and only 1 % of the boreal and temperate species.